Towards occupational enablement: experiences of the ECD practitioners regarding the crosstrainer programme - Homan, Adeleigh (University of the Free State, 2018)
Introduction: South African Early Childhood Development (ECD) practitioners are not adequately trained and have been regarded as one of the primarily important aspects of concern in the South African ECD setup. Focussing on the adequacy and qualification of the ECD practitioners through training, mentoring and support are core components of an effective ECD system. This necessity of transformation within the South African ECD sector, as well as the lack of resources and systems to facilitate improvement, enthused the Crossroads Educational Foundation to mobilise the Crosstrainer Programme (CTP). The CTP is an ECD centre-based Early Childhood Development programme providing early learning stimulation for children from three to six years of age. Importantly, the CTP is not solely purposed to improve the development of children, but inherently pursues to enable the ECD practitioners in their occupation. In occupational therapy, human occupation is considered the core domain of concern and enabling occupation as the core competency of occupational therapists. A broader global and social responsibility towards the issues of inequity and poverty is recognised, as occupational therapy has the potential to benefit the wider society as well as the individual. Moreover, being a change agent is attributed as a central role and proficiency of occupational therapists. Arguably, it is imperative for South African occupational therapists to become involved in the ECD change. Enabling the occupation of the ECD practitioners through training, mentoring, and providing support will potentially transform the ECD sector and support the efforts of the South African government and other organisations towards this transformation. Although the Crosstrainer Programme is aimed at enabling, it is important to learn how these ECD practitioners experience this intended enablement. Purpose: The purpose of the research was to describe the experiences of the ECD practitioners regarding the occupational enablement through the CTP. Methodology: To generate this rich data, a descriptive qualitative research design was followed within a constructivist paradigm. Semi-structured interviews and demographic questionnaires were utilised. The data generated from the interviews were coded, analysed and interpreted, whilst the demographic information informed the context essential towards understanding the occupational enablement of the participants. Findings: Three themes were derived from the data including The Great Imbalance, Enabling Occupation, and Disabling Occupation. The Great Imbalance primarily described the context of the participants, informing their occupational enablement. Enabling Occupation portrayed the facilitating factors of the CTP towards the occupational enablement of the ECD practitioners. It was found that the CTP enables the occupation of the ECD practitioners through all six enablement foundations namely, choice, risk and responsibility; client participation; visions of possibility; change; justice; and power-sharing. Moreover, the CTP contributed to their occupational enablement within doing, being, becoming and belonging as ECD practitioners. The last theme, Disabling Occupation revealed the factors hindering their occupational enablement, proving that some improvements are necessary. Conclusions: In essence, it was found he CTP predominantly facilitates enablement rather than hinders it, with room for improvement. Upon the necessary addition, adjustment, and increase, the enablement through the CTP could improve. This study has shown that these ECD practitioners still need much assistance; and designed programmes developing their skill and knowledge through daily guidance have been deemed successful in doing so. For the holistic development of children and the ECD practitioners, the CTP, also in conjunction with other programmes, could be a valuable programme to consider.
Dissertation (M. (Occupational Therapy))--University of the Free State, 2018
Keywords: Occupational therapy; Early Childhood Development; ECD; Crosstrainer programme; Occupation; Enablement; Enabling occupation; ECD practitioners; Mahikeng